DIFFERENTIAL DIAGNOSTICS OF INFECTIOUS EXANTHEMAS IN CHILDREN - D. Yu. Ovsyannikov (Детские инфекции (Москва), 2015)
The lecture is devoted to the problem of differential diagnosis of infectious exanthemas in children. Information about differential-diagnostic sings of infectious and non-infectious exanthemas is present. Differential diagnosis is proposed on the basis of morphological elements identified in objective research. Presents possible infectious and non-infectious causes of rashes which are characterized by different primary (spot, papula, blister, knob, knot, bubble, abscess, bladder) and secondary (scale, erosion, ulcer) morphological elements.